Bioglass functionalization of laser-patterned bioceramic surfaces and their enhanced bioactivity. Issue 12 (December 2018) - Marin, Elia; Horiguchi, Satoshi; Zanocco, Matteo; Boschetto, Francesco; Rondinella, Alfredo; Zhu, Wenliang; Bock, Ryan M.; McEntire, Bryan J.; Adachi, Tetsuya; Bal, B. Sonny; Pezzotti, Giuseppe
Abstract: The surfaces of silicon nitride ( β -Si3 N4 ) and zirconia toughened alumina (ZTA) were patterned using a high-energy laser source, which operated at a wavelength of 1064 nm. The patterning procedure yielded a series regular, cylindrical cavities 500 and 300 μm in diameter and depth, respectively. These cavities were subsequently filled with bioglass mixed with different fractions of Si3 N4 powder (0, 5, and 10 mol.%) to obtain bioactive functionalized bioceramic surfaces. The laser-patterned samples were first characterized using several spectroscopic techniques before and after functionalization, and then tested in vitro with respect to their osteoconductivity using a human osteosarcoma cell line (SaOS-2). After in vitro testing, fluorescence microscopy was used to address the biological response and to estimate osteopontin and osteocalcin protein contents and distributions. The presence of bioglass greatly enhanced the biological response of both ceramic surfaces, but mainly induced production of inorganic apatite. On the other hand, the addition of minor fraction of Si3 N4 into the bioglass-filled holes greatly enhanced bio-mineralization and stimulated the SaOS-2 cells to produce higher amounts of bone extracellular matrix (collagen and proteins), thus enhancing the osteopontin to osteocalcin ratio. It was also observed that the presence of a fraction of Si3 N4 in the powder mixture filling the holes bestowed more uniform cell colonization on the otherwise bioinert ZTA surface.